Development Of Interasolve-Book Learning Media for IPAS Subject in Elementary Schools - Syahyadi, Deni; Firdaus, Fery Muhammad; Nirmala, Sri Dewi (Universitas Pakuan, 2025)
The Merdeka Curriculum emphasizes the importance of student-centered learning and the development of 21st century competencies. This is in line with the development of the times that require individuals to have the ability to think critically, creatively, collaboratively, and communicate (4C). To achieve this goal, the use of innovative learning media is very relevant. InteraSolve-Book, an interactive learning media, provides opportunities for students to learn actively, and provides a better understanding for students with various learning styles in the material on ecosystem imbalance in grade V of Elementary School. This development research uses the 4D method from Tiagarajan through 4 stages: define, design, develop and disseminate. Feasibility data was obtained from linguist validation instruments, learning media experts, and learning material experts. Meanwhile, practicality data was obtained from a questionnaire of model teachers who carried out learning with IntersSolvE-Book. The feasibility level was obtained at 73.21% for language, 97.5% for media and 86.54% for learning materials. In terms of practicality, InteraSolvE-Book got a 98% result. Thus, InteraSolvE-Book has been tested to be feasible and practical to be used in learning.